2018
DOI: 10.1186/s12917-018-1387-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of feline renal cortical fibroblast cultures and their transcriptional response to transforming growth factor β1

Abstract: BackgroundChronic kidney disease (CKD) is common in geriatric cats, and the most prevalent pathology is chronic tubulointerstitial inflammation and fibrosis. The cell type predominantly responsible for the production of extra-cellular matrix in renal fibrosis is the myofibroblast, and fibroblast to myofibroblast differentiation is probably a crucial event. The cytokine TGF-β1 is reportedly the most important regulator of myofibroblastic differentiation in other species. The aim of this study was to isolate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…Recently published data from feline renal cortical fibroblast cultures confirm our results, as incubation of these cells with TGF-β1 also increased the expression of COL1 , α-SMA and CTGF . 26 Although the CRFK cells could have changed over time from more of an epithelial to a somewhat more fibroblastic phenotype, the results of the present study clearly demonstrated the formation of myofibroblasts by TGF-β1 via increased expression of COL1 , α-SMA and CTGF .…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…Recently published data from feline renal cortical fibroblast cultures confirm our results, as incubation of these cells with TGF-β1 also increased the expression of COL1 , α-SMA and CTGF . 26 Although the CRFK cells could have changed over time from more of an epithelial to a somewhat more fibroblastic phenotype, the results of the present study clearly demonstrated the formation of myofibroblasts by TGF-β1 via increased expression of COL1 , α-SMA and CTGF .…”
Section: Discussionsupporting
confidence: 41%
“…These results further support the profibrotic effect of TGF-β1 in the kidney demonstrated by earlier (clinical) studies in cats. 2628 The CRFK cells showed almost no expression of the AT 1 receptor, precluding induction of these EMT marker genes by AT-II incubation. As AT-II contributes to renal fibrosis by various mechanisms, of which one is by TGF-β1 gene induction, it can be hypothesised that AT-II would show similar results to TGF-β1 if the AT 1 receptor was expressed more in CRFK cells.…”
Section: Discussionmentioning
confidence: 97%
“…Transforming growth factor beta1 (TGF-β1) is one of the pro-fibrotic cytokines and is thought to be the primary mediator driving the progression of fibrosis, glomerulosclerosis and especially mesangial cell phenotype transformation in diabetic nephropathy (DN) [ 1 , 2 ]. TGF-β1 directly stimulates the transcription of extracellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 99%
“…Cryopreserved CRFK cells were purchased at passage 185 (CCL-94, ATCC) and cultured according to the manufacturer's protocol 1. FPTEC, FCF and human umbilical vein endothelial cells (HUVEC) were cultured for comparison as previously described (Lawson et al, 2018a; Lawson et al, 2018b). Cells were assessed for the expression of the marker proteins cytokeratin AE1/AE3 (Dako), vimentin (Dako), desmin (Dako), von Willebrand factor (vWF)(Dako), CD44 (ABD Serotec) and CD29 (Bio-rad) by immunofluorescence, and cytokeratin AE1/AE3, vimentin and vWF by western blotting as previously described (Lawson et al, 2018a).…”
mentioning
confidence: 99%
“…RNA was extracted from CRFK, FPTEC and FCF using a column based kit (Genelute™ Mammalian Total RNA Miniprep Kit, Sigma-Aldrich). Expression of S100A4 was quantified by RT-qPCR and normalised to GAPDH/RPS7 using previously published primers (Lawson et al, 2018b). Data are expressed as mean fold change relative to untreated control and statistical significance was evaluated by one-way analysis of variance (ANOVA) with post-hoc Dunnet's test.…”
mentioning
confidence: 99%